Formação de professores das séries iniciais: o pedagogo em questão - Leite, Aline Fernanda Ventura Sávio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aimed to show the importance of teacher for the learning process in the early years of elementary shool proposing a teaching science based on a constructivist reading. This paper will discuss a brief history of the Faculty of Education, the importance of continuing education for the effective teaching of natural sciences as well as their content and methodologies. We seek also explain about the history of natural science education pointing to existing legislation that supports this disciplines and Piaget's ideas on education. This research involves three objects of study through a qualitative approach to records and interviews proposed by Ludke; André; (1986) First we analyze and interview with acting teachers in a Municipal School of Interior of. Then we study the initial training of teachers through documents that make up the course as: curriculum, the menu of disciplines, political and pedagogical project, the internet pages of presentation, educational programs and projects. We will also consider the natural science content taught from first to fifth year of elementary school for an education system. In is expected that the data pointed to this research contribute to science education, for training and teacher's identify construction as well as assist in their continuing education

Esta pesquisa teve como objetivo mostrar a importância do pegagogo para o processo ensino aprendizagem nos anos iniciais do Ensino Fundamental propondo um ensino de ciências fundamentado em uma leitura construtivista. O presente trabalho abordará um breve histórico do curso de Pedagogia, a importância da formação continuada para o efetivo ensino de ciências naturais, assim como, seus conteúdos e metodologias. Buscaremos também explanar sobre a história do ensino de ciências naturais apontando a legislação vigente que ampara esta disciplina e as ideias de Piaget sobre educação. Esta pesquisa envolve três objetos de estudo por meio de uma abordagem qualitativa de análise documental e entrevista proposta por Ludke; André; (1988) Primeiramente analisaremos uma entrevista realizada com pedagogos atuantes em uma Escola Municipal do Interior de São Paulo. Em seguida estudaremos a formação inicial dos pedagogos por meio de documentos que compõem o curso como: matriz curricular, emenda das disciplinas, projeto político e pedagógico, páginas da internet de apresentação, programas e projetos pedagógicos. Analisaremos também os conteúdos de ciências humanas ministrados do primeiro ao quinto ano do Ensino Fundamental por um sistema de ensino. Espera-se que os dados apontados nesta pesquisa contribuam para o Ensino de Ciências, para a formação e construção da identidade do pedagogo assim como o auxiliar em sua formação continuada
Training of teachers in early grades: the educator in question
Keywords: Construtivismo (Educação); Ensino; Ciencia; Ensino fundamental; Professores; Constructivism (Education)